Typy cyrkulacji atmosfery a rodzaje chmur w Poznaniu - Szyga-Pluta, Katarzyna (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2009)
The frequency of appearance of cloud genera was analyzed taking into consideration their associated types of circulation. The study is made on the basis of diurnal climatological observations carried out in Poznań in years 1971-1990. The Lityński objective classification of circulation types was used. The research results prove that the cloud genera appear throughout the year depending on the atmospheric circulation. High clouds are the most frequent during the anticyclonic types of circulation (table 1). As, Ns, St and Cb clouds are associated with the cyclonic circulation. Ac, Sc and Си clouds form independently of the circulation type which shows the biggest influence of the local conditions on the specific clouds. Among the anticyclonic types of circulation the type NWA is conducive to forming of Ci, Cc, Ac, Sc, Си and Cb clouds (table 2, fig. 1). Cs clouds are connected mainly to the SWA circulation. The air inflow from west is favourable to form the As and Ns clouds. St clouds appear most often during the NA circulation. During the intermediate circulation types, high and middle clouds form most frequently when the air flows from the SW direction (table 3, fig. 2). Sc, St and Си clouds favour to appear during the NWo circulation. Cb clouds form mainly in connection to the NE0 circulation. In the midst of the cyclonic circulation the type SWc is conductive to occurring of: Ci, Cs, Ac, As, Ns and Sc types of clouds (table 4, fig. 3). Cc, St, Си and Cb clouds are mainly associated with the NWc circulation.